Synthesis of a Series of α, β-Unsaturated Ketoximes and their Corresponding Acetate Esters - Jihad, Tahani W; Alkazzaz, Abdulkhalik S. (Iraqi Journal of Science, 2022)
A series of 1,3-diarylprop-2-en-1-one oximes (7-12) were synthesized via reaction of 1,3-diarylprop-2-en-1-one (1-6) with NH2OH. HCl in dry pyridine. In order to produce the required products (13-18) as anti-isomers, these products (7–12) were then treated with acetic anhydride in dry pyridine. Different substitutes are maintained, resulting in the separation of different products in different yields The recently produced esters are thought to be useful as building blocks for the synthesis of substituted pyridines and many other nitrogen-holding complexes, which are elaborate structures in medicinal chemistry and present in a variety of pharmaceutical medications. The synthesized products were characterized and their structural details were clarified using 1H NMR spectroscopy of a representative one sample ester and oxime, (FT-IR, UV) investigations, and melting point analysis. Besides the elemental micro analysis (C, H, N) of the same samples, the suggested mechanisms for these reactions were investigated according to these calculations.